(untitled) (Journal of Current and Advance Medical Research, 2022)
Background: Snake bite and the subsequent envenomation is an important health hazard which may lead to fatality in rural areas of Bangladesh. Objective: This study was conducted to evaluate the epidemiology, clinical profile, treatment and outcome for patients with snake bite admitted in the intensive care unit of Dhaka Medical College Hospital, Bangladesh. Methodology: This prospective cohort study was conducted in the Department of Anaesthesia, Analgesia, Palliative and Intensive Care Medicine, Dhaka Medical College, Dhaka, Bangladesh from May 2019 to April 2020 for a period one year. The patients of snake bite were treated in the Intensive care unit, Dhaka Medical College Hospital, Dhaka, Bangladesh. A questionnaire, containing information on bite, physical examination and identification of snake was used. Results: A total number of 23 patients of snake bite were treated in the Intensive care unit. Among the patients, 16 (69.56%) were bitten by cobra, 2 (8.6%) were suspected to be bitten by krait and 5(21.7%) cases had Russel viper bite. Tight tourniquet was used in 15(65.21%) cases. Among the patients 18(78.26%) patients were observed with the features of neurotoxicity with or without local envenoming. Among all patients, one patient required two doses of ASV, another patient needed 3 doses; but the other patients were found to be improved after getting a single dose of ASV. However, 15 patients needed ventilator support. The mean duration of ventilator support was 4.8 days. The mortality was 30.43% (7 patients). Out of these 7 patients, 4 patients died due to acute renal failure with DIC. Conclusion: Neuroparalytic Cobra envenomation is accounted for the highest incidence of venomous bites in the present study. Journal of Current and Advance Medical Research, January 2022;9(1):48-55